PENERAPAN BELLMANN-FORD ALGORITHM DALAM PENCARIAN RUTE TERPENDEK DISTRIBUSI SUKU CADANG DI KOTA BANDUNG : PENERAPAN BELLMANN-FORD ALGORITHM DALAM PENCARIAN RUTE TERPENDEK DISTRIBUSI SUKU CADANG DI KOTA BANDUNG - Budi Santosa Chulasoh; Muhammad Ilham Bukhori; Prafajar Suksessanno Muttaqin (Universitas Widyatama, 2025)
FDX company engaged in the distribution of two-wheeled vehicle spare parts. Two-wheeled vehicle spare parts are components or elements specifically designed and manufactured to replace original parts of two-wheeled vehicles that are damaged, worn out, or no longer functioning optimally. These spare parts include various mechanical, electrical, and structural elements necessary to ensure vehicle performance, safety, and operational continuity in accordance with factory standards and applicable safety regulations. Based on existing data, there has been a noticeable increase in the demand for spare part deliveries in the city of Bandung. Consequently, the company requires an optimal route planning strategy to ensure that the products are delivered within the specified time frame and at minimal cost. This research aims to determine the shortest delivery route for distributing two-wheeled vehicle spare parts to optimize both travel distance and transportation costs. The algorithm is used to construct a graph that identifies the shortest path by evaluating all possible routes from the origin to the destination. Future studies may apply Dijkstra’s algorithm or the Gabow algorithm to compare and potentially obtain more optimal results.